Knowledge, attitude, practices and their associated factors towards HIV/AIDS among residents of Benadir Region, Somalia - Dahie, Hassan Abdullahi; Heyle, Abdullahi Ali (Advances in Social Sciences Research Journal, 2019)
HIV/AIDS is a global challenge that has threatened the very existence of the human race. There were approximately 36.7 million people worldwide living with HIV/AIDS at the end of 2016 of whom an estimated 1.8 million individuals worldwide became newly infected with in the year 2016. From the onset of the epidemic 76.1 million had become infected, and 35.0 million had died. Of the 36.7 million living with HIV, 19.5 million were accessing anti-retroviral therapy. The African population represents almost 70% of total HIV cases worldwide where the majority is young Africans aged 15-24. Furthermore, Sub-Saharan Africa is the most affected region, with an estimated 25.6 million people living with HIV of which about 66% of new infection occurred in Sub-Sahara in 2015 (UNAIDS, 2016). Although, Somalia is believed to be currently a low human immunodeficiency virus (HIV) prevalent country. However, the risk factors are widespread and the number of at-risk population is also rising, which warrants special policy attention. Objective of the study: The objective of the study was to assess the knowledge, attitude, practices, and its associated factors towards HIV/AIDS among residents of Benadir Region, Somalia. Methods: A community based cross-sectional study was conducted from 1st April to 31st September, 2018 among 585 community members of Benadir Region. Data was collected using pretested structured face-to-face interview after taking informed written consent. Two-stage cluster sampling and systematic random sampling were used to select the districts and the households respectively. Result: Five hundred and eighty-five (585) respondents participated and gave a response rate of 96.7%. Of the 585 respondents, 309 (52.8%) were females while 276 (47.2%) were males. The respondents aged between 14-78 years. It was found out that 70% of the participants were knowledgeable, 50.8% and 26.3% had favourable attitude and good practice respectively. With regard to education level, being able to read & write, 7 times (AOR=7.33, CL= 3.74, 14.34), grade 1-4, 5 times (AOR=4.71,CL= 2.82, 7.88), grade 5-8 3 times (AOR=3.43, CL=1.42, 8.29) and college & above, 2 times (AOR=1.93, CL=1.17, 3.20) were more likely to have HIV/AIDS knowledge as compared to those who were illiterate. Being a male was 0.66 times (AOR=0.66, CL=0.48, 0.91) less likely to have a favourable attitude towards HIV/AIDS compared to females. Similarly, belonging to 35-44 age group was 4 times (AOR=3.57, CL=1.30, 9.83) more likely to have favourable attitude. Having family income of 100-300 USD was 2 times (AOR=2.20, CL=1.04, 4.62), having monthly income 301-500 USD was 3 times (AOR=3.06, CL= 1.53, 6.13) more likely to have a favourable attitude towards HIV/AIDS. Conclusion: Concerning participants’ Knowledgeability, 70% of the participants were knowledgeable, 50.8% and 26.3% had favourable attitude and good practice respectively. This shows that there is considerable limited knowledge, attitude and practices. Gender, age, marital status, level of education, occupation and monthly family income showed significant association. Recommendation: There is a need for developing policies & strategies to raise community awareness about HIV/AIDS, to involve active community members and religious leaders to be positive role models in influencing people’s behaviour.